ENT600 : petrol payment mechanism / Mohd Yusof Mohamed Fahmy, Mohamad Izwan Roselan and Mohammad Akhil Abdul Aziz - Mohamed Fahmy, Mohd Yusof; Roselan, Mohamad Izwan; Abdul Aziz, Mohammad Akhil (2018)
Years before, petrol station is the place where people refuel their car and purchase others type of lubricant oil. The time has changed. Nowadays, petrol station acts as aone stop center, not only selling fuel but also other services such as food & beverages, ATM, utilities bill payments and more. All these new services had attracted more people to come to the petrol station. Due to these, the workload to the cashier at the petrol station's counter had increased. The cashier had to entertain other services besides fuel purchase transaction.